Differential impact of a multimodal versus pharmacological therapy on the core symptoms of attention deficit/hyperactivity disorder in childhood. (December 2016) - Amado, Laura; Jarque, Sonia; Ceccato, Roberta
Abstract: The aim of this study was to analyze the relative and differential efficacy of a combined versus medical treatment to reduce the symptoms of ADHD children in the school and family environment. A total of 100 subjects participated: 20 children with ADHD, their 40 parents and their 40 teachers. Half of the subjects were assigned to the drug group and half to the combined (drug plus psychosocial, psychoeducational intervention with teachers and mothers/fathers). Results: The group analyses indicated that both treatments were effective, without significant differences between them. Individualized clinical analyses indicated that higher percentages of improvement and normalization were obtained in the children in the combined group than in the drug only group. Our findings point to the desirability of implementing long-lasting multimodal, multicontextual interventions for ADHD in childhood.